HOMI JEHANGIR BHABHA: HIS COLLABORATORS, CITATION IDENTITY, AND HIS CITATION IMAGE MAKERS - T., Swarna; V.L., Kalyane; Kumar, Vijai (Malaysian Journal of Library and Information Science, 2017)
In this paper, we studied synchronous references (references in the same papers) and diachronous citations (citations to the papers) of the renowned theoretical physicist, Homi Jehangir Bhabha. We utilized the Science Citation Index (SCI) on CD from 1982 – 2006. We identified his coauthors, his most cited works, citation identity (authors whom he had cited) and citation image makers (authors citing him). Bhabha published his first paper in 1933 at the age of 24 and the last paper in 1966, the year of his demise. His 66 papers could be categorized into nine fields: Cosmic ray physics (18 papers); Elementary particle physics, and Field theory (14 papers each); Quantum electrodynamics (6 papers); Nuclear physics (4 papers); General, and Interaction of radiation with matter (3 papers each); and Mathematical physics and General physics (2 papers each). He collaborated with 18 authors in 18 papers; the remaining 48 papers were single-authored. His citation identity consisted of 212 different authors, of whom six were Nobel laureates. He received 328 citations to his works, his overall citation rate being 10.6 per cited paper and the highest citation rate was 21.2 to his papers in the field of Elementary particle physics. His most often cited paper was in Quantum electrodynamics with 54 citations. His image makers comprised 537 different authors. Bhabha has the distinction of being cited by at least two Nobel laureates, P.M.S. Blackett and H. Yukawa in their respective Nobel lectures.